2020
DOI: 10.3390/ma13204544
|View full text |Cite
|
Sign up to set email alerts
|

Role of PVDF in Rheology and Microstructure of NCM Cathode Slurries for Lithium-Ion Battery

Abstract: A binder plays a critical role in dispersion of coating liquids and the quality of coating. Poly(vinylidene fluoride) (PVDF) is widely used as a binder in cathode slurries; however, its role as a binder is still under debate. In this paper, we study the role of PVDF on the rheology of cathode battery slurries consisting of Li(Ni1/3Mn1/3Co1/3)O2 (NCM), carbon black (CB) and N-methyl-2-pyrrolidone (NMP). Rheology and microstructure of cathode slurries are systemically investigated with three model suspensions: C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…[ 17–21 ] PVdF and its derivatives have been one of the most commonly used binder materials in commercial LIBs due to their outstanding electrochemical stability, excellent binding properties, and good wettability with the electrolyte. [ 22,23 ] However, its electrically/ionically insulating nature and the use of the toxic organic solvent, N ‐methyl‐2‐pyrrolidone (NMP), for this kind of electrode fabrication suggests an active search of more conductive and environmentally friendly polymeric materials. [ 24,25 ] In recent years, several kinds of alternative polymeric materials have been investigated for high‐voltage cathodes, [ 26–30 ] such as lithium polyacrylate (LiPAA), [ 29 ] poly (acrylic acid) (PAA)‐based amphiphilic bottlebrush polymers (BBPs), [ 30 ] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17–21 ] PVdF and its derivatives have been one of the most commonly used binder materials in commercial LIBs due to their outstanding electrochemical stability, excellent binding properties, and good wettability with the electrolyte. [ 22,23 ] However, its electrically/ionically insulating nature and the use of the toxic organic solvent, N ‐methyl‐2‐pyrrolidone (NMP), for this kind of electrode fabrication suggests an active search of more conductive and environmentally friendly polymeric materials. [ 24,25 ] In recent years, several kinds of alternative polymeric materials have been investigated for high‐voltage cathodes, [ 26–30 ] such as lithium polyacrylate (LiPAA), [ 29 ] poly (acrylic acid) (PAA)‐based amphiphilic bottlebrush polymers (BBPs), [ 30 ] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous study, we confirmed that the PVDF binder in the NMP-based cathode slurry plays a major role in increasing the matrix viscosity without significantly affecting the interaction between the cathode active materials and the conductive particles. 16 Therefore, the surface properties of the active material and the conductive particles are very important in the cathode slurry in forming the microstructure. However, the cathode active material and the conductive particle show quite different surface properties.…”
Section: Effect Of Matrixmentioning
confidence: 99%
“…The dispersion state and the storage stability of the manufactured electrode slurry are very important as they directly affect the subsequent electrode process as well as the electrochemical performance of the batteries. Therefore, research studies on dispersion stability have been actively conducted. …”
Section: Introductionmentioning
confidence: 99%
“…In an isotropic medium, the Stokes-Einstein equation D Binder = kT/3πµd can be developed to predict the effective diffusion coefficient, where µ is the viscosity of slurries, kT is thermal energy, and d is the effective diameter of BC. Consider the relation of the viscosity between CMC [41], SA [42], and PVDF [43] at a zero-shear state, we estimate that the diffusion coefficient of BC in the CMC-SBR slurry and SA slurry is 3D PVDF and 10D PVDF . Based on the tensile experimental data of SA and CMC-SBR [36], the enthalpy of vaporization of water 2257 kJ/kg [38], we compared the binder distribution and shear modulus of dried electrode films composed of PVDF, CMC-SBR, and SA, respectively, as seen in Figure 4.…”
Section: Gradient Distributed Physical Properties Across Electrode Thicknessmentioning
confidence: 99%